METODE PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR DENGAN KURIKULUM MERDEKA - Tasma Rahmah; Tiwi Sri Pujiawati; Veli Sifa Hendayani; Nurfitria (JOEL: Journal of Educational and Language Research, 2024)
Indonesian language classes in elementary schools mainly teach children how to communicate in Indonesian Learning Indonesian in elementary schools aims to improve students' Indonesian language communication skills, both oral and written. The aim of elementary school is to provide opportunities for students to achieve a higher level of education One effort to achieve this goal is to increase student learning success. The Merdeka Curriculum offers an approach that gives schools and teachers greater freedom to adapt learning materials to local realities. This research aims to describe the implementation of the Independent Curriculum, evaluate its impact on the learning process, and identify supporting factors and obstacles faced in its implementation